Bamboo Shelters in Kerala : Problems and Prospects - Muraleedharan, P. K.; Anitha, V.; Sreelakshmi, K.; Simon, T. D. (Indian Forester, 2003)
The National Housing Policy announced by the Government of India in 1994, emphasised the construction of low cost houses with locally available materials. In this context, bamboo as a construction material, assumes greater significance. Bamboo has been used traditionally by various sections of society in Kerala since times immemorial. Of late, there has been a significant decline in the number of bamboo houses in the State. An attempt was made in this study to assess the socio-economic factors contributing to the non-preference of bamboo as a coustruction material. The study is based on sample survey conducted among 180 households with bamboo houses. Although bamboos are available in plenty, the housing sector experiences severe shortage of the same as the pulp and paper industry purchases bamboos by offering higher prices. About 95 per cent of the selected households preferred tiled bamboo houses to thatched ones because of durability and low maintenance cost. Low income of the people and non-availability of good quality bamboos constitute two major constraints in the promotion of bamboo houses.